Introduction to risk management and insurance - DORFMAN, Mark S (PRENTICE HALL, 2008)
This book focuses on problem-solving from managerial, consumer, and societal perspectives. It emphasizes both the business managerial aspects of risk management and insurance and the numerous consumer applications of the concept of risk management and insurance transaction.